Ideologia e educação na crise do capitalismo contemporâneo - Silva, Renalvo Cavalcante (2012)
The understanding of reality has been followed by the philosophers from the classical period to modern times. However, for a long time the possibilities to understand material reality were circumscribed to the epistemic logical-epistemological perspective, without due considerations regarding objectivity, which are based on social relations in the world of men. Only through the historical and dialectical materialism of Karl Marx himself could understand the relationship between objective reality and human consciousness, escaping the theoretical Hegel's idealist and critique of this theory undertaken by the Hegelians of the left. Marx and Engels (2007) realized that the class that holds the dominant material power also keeps the dominant spiritual power, so that the values, ideas, behavior, culture, politics, education etc. meet the material needs of a particular mode of production. But that does not mean that ideology is an exclusive phenomenon of class society, as in primitive societies it fulfilled the function of resolving conflicts and ensured social cohesion necessary to the survival of the members of that kind of community. The objective of this research, from the ontological critique of the work is to understand how to manifest the ideological aspects of education in the contemporary capitalist crisis, identified by István Mészáros (2002) as a structural crisis. From these assumptions, it is understood that education has been an important instrument of ideological internalization of apprehension and knowledge that meet the interests of the ruling class, which does not remove the possibility of opposition to the paradigms imposed by capital, because, unlike the critical-thinking reprodutivists, education, broadly or restrictively, not only plays the dominant ideas, but also offers the possibility of developing a critical and radical position against the power exercised by the capitalist economic system. Thus, as should be ordered to reprodutivists perspective of thinkers, we must likewise reject the inexorable logic of capitalism advocated by ideologues who advocate the impossibility of overcoming the social relations established by the liberal economic order. Therefore, this research believes that both theories of the end of history as the end of ideologies represent the imposition of ideological class that dominates in the face of its structural crisis, being intended to stay this mode of production, even if it means forwarding humanity to barbarism.